Inflammatory signaling on cytochrome P450-mediated drug metabolism in hepatocytes - Wang, Xiaokang; Rao, Jiaoyu; Tan, Zhiyi; Xun, Tianrong; Zhao, Jingqian; Yang, Xixiao (Frontiers in Pharmacology, 2022)
Cytochrome P450 (CYP450) enzymes are membrane-bound blood proteins that are vital to drug detoxification, cell metabolism, and homeostasis. CYP450s belonging to CYP families 1–3 are responsible for nearly 80% of oxidative metabolism and complete elimination of approximately 50% of all common clinical drugs in humans liver hepatocytes. CYP450s can affect the body’s response to drugs by altering the reaction, safety, bioavailability, and toxicity. They can also regulate metabolic organs and the body’s local action sites to produce drug resistance through altered drug metabolism. Genetic polymorphisms in the CYP gene alone do not explain ethnic and individual differences in drug efficacy in the context of complex diseases. The purpose of this review is to summarize the impact of new inflammatory-response signaling pathways on the activity and expression of CYP drug-metabolizing enzymes. Included is a summary of recent studies that have identified drugs with the potential to regulate drug-metabolizing enzyme activity. Our goal is to inspire the development of clinical drug treatment processes that consider the impact of the inflammatory environment on drug treatment, as well as provide research targets for those studying drug metabolism.